Optimalisasi Raw Material pada Proses Produksi Knalpot Mobil (Studi Kasus: PT Elysium Autotech Surabaya) - Manullang, William Kevin Feriyanus; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to optimize the utilization of raw materials in the exhaust production process at PT Elysium Autotech Surabaya. The main issue faced by the company is the excessive leftover cuts of stainless-steel pipes and plates, which cannot be reused due to mismatched dimensions. These material wastes contribute to increased production costs and reduced efficiency. By analyzing material specifications, product structure, Bill of Materials (BoM), and current cutting techniques, this study identifies critical points where raw material inefficiencies occur, particularly in the cutting process for downpipe and frontpipe components. The results indicate that leftover pipe cuts from the frontpipe production can be repurposed for downpipe manufacturing, reducing the need for new raw materials. The implementation of optimized cutting patterns leads to substantial cost savings, reaching Rp41,250,000 per month for Fortuner exhaust production and Rp75,000,000 per month for Kijang Innova. This optimization significantly enhances material efficiency and reduces overall production costs.